Investigating the shock histories of lunar meteorites Miller Range 090034, 090070, and 090075 using petrography, geochemistry, and micro‐FTIR spectroscopy - Martin, Dayl J. P; Pernet‐Fisher, John F; Joy, Katherine H; Wogelius, Roy A; Morlok, Andreas; Hiesinger, Harald (Meteoritics & planetary science, 2017)
Fourier transform infrared (FTIR) spectroscopy and cathodoluminescence (CL) imaging techniques, combined with electron microprobe analyses, have been used to determine the physical state of feldspathic phases that have been subject to varying levels of shock in the grouped lunar meteorites Miller Range 090034, 090070, and 090075. Six feldspathic phases have been identified based on spectral, textural, and chemical properties. A specific infrared wavelength band ratio (1064/932 cm−1 equivalent to 9.40/10.73 μm), chosen because it can distinguish between some of the feldspathic phases, can be used to estimate the pressure regimes experienced by these phases. In addition, FTIR spatial mapping capabilities allow for visual comparison of variably shocked phases within the samples. By comparing spectral and compositional data, the origin and shock history of this lunar meteorite group has been determined, with each of the shocked feldspathic phases being related to events in its geological evolution. As such, we highlight that FTIR spectroscopy can be easily employed to identify shocked feldspathic phases in lunar samples; estimate peak shock pressures; and when compared with chemical data, can be used to investigate their shock histories.